Kajian Kritis Tentang Pemikiran Emanasi dan Hubungannya dengan Sains Modern (Indo-MathEdu Intellectuals Journal, 2024)
This article aims to find out the thought of emanation and its relationship to modern science. This article uses a qualitative approach with the literature study method. This method is intended to examine various sources relevant to the focus of this research. The main sources of research data are scientific books and articles published in various scientific journals and indexed on the google scholar database. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of the analysis show that the philosophical basis of the concept of emanation is the desire to avoid God from the pluralist nature in order to purify the oneness of God from all material things. The creation of the cosmos with the theory of emanation will confirm the opinion that this realm is qadim in the sense that it experiences continuous creation with different faces and shapes. It is not qadim in the sense that it is equal to God the creator who is qadim in nature. The theory of emanation in the world of modern science finds its relevance in the Big Bang theory which says that nature is created from a big bang process that begins with a heating process so that it develops until it emits a loud sound